2004
DOI: 10.1083/jcb.200404015
|View full text |Cite
|
Sign up to set email alerts
|

Dynein/dynactin regulate metaphase spindle length by targeting depolymerizing activities to spindle poles

Abstract: During cell division metaphase spindles maintain constant length, whereas spindle microtubules continuously flux polewards, requiring addition of tubulin subunits at microtubule plus-ends, polewards translocation of the microtubule lattice, and removal of tubulin subunits from microtubule minus-ends near spindle poles. How these processes are coordinated is unknown. Here, we show that dynein/dynactin, a multi-subunit microtubule minus-end–directed motor complex, and NuMA, a microtubule cross-linker, regulate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
186
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(207 citation statements)
references
References 31 publications
19
186
2
Order By: Relevance
“…Because of technical limitations of the gene knockdown approach, we cannot exclude the possibility that other kinesins and/or dynein might also be involved in mitosis and cytokinesis. Indeed, dynein has previously been implicated in spindle formation and mitosis (Echeverri et al, 1996;Goshima and Vale, 2003;Gaetz and Kapoor, 2004). However, our study and others (Kittler et al, 2004) indicate that depletion of dynein by siRNA does not cause any mitotic or cytokinetic abnormalities.…”
Section: Discussioncontrasting
confidence: 53%
“…Because of technical limitations of the gene knockdown approach, we cannot exclude the possibility that other kinesins and/or dynein might also be involved in mitosis and cytokinesis. Indeed, dynein has previously been implicated in spindle formation and mitosis (Echeverri et al, 1996;Goshima and Vale, 2003;Gaetz and Kapoor, 2004). However, our study and others (Kittler et al, 2004) indicate that depletion of dynein by siRNA does not cause any mitotic or cytokinetic abnormalities.…”
Section: Discussioncontrasting
confidence: 53%
“…The action of Kif2A has been more controversial. Some studies implicate the protein in controlling MT flux (Gaetz and Kapoor, 2004;Ganem et al, 2005), whereas other studies clearly show that it is not required for MT flux (Cameron et al, 2006;Ohi et al, 2007). More recently, it has been demonstrated that although both MCAK and Kif2A can depolymerize MTs with nearly equal efficiency, they cannot substitute for each other functionally during spindle assembly in Xenopus egg extracts (Ohi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in vertebrates and fruitflies have suggested that these proteins are transported poleward by cytoplasmic dynein. Inhibition of dynein in Xenopus egg extract spindles or Drosophila tissue culture cells causes kinesin-13s that are normally associated with poles to become spread across the spindle (Gaetz and Kapoor 2004;Morales-Mulia and Scholey 2005). We have also found that the accumulation of KLP10A on spindle poles involves a second kinesin-13 family member, KLP59D.…”
Section: Mechanism Of Flux I: Depolymerization Of Spindle Pole-focusementioning
confidence: 54%